Conditional hepatocyte ablation of PDIA1 uncovers indispensable roles in both APOB and MTTP folding to support VLDL secretion - Zhouji Chen; Shiyu Wang; Anita Pottekat; Alec Duffey; Insook Jang; Benny H. Chang; Jaehyung Cho; Brian N. Finck; Nicholas O. Davidson; Randal J. Kaufman (Elsevier, 2024)
Objectives: The assembly and secretion of hepatic very low-density lipoprotein (VLDL) plays pivotal roles in hepatic and plasma lipid homeostasis. Protein disulfide isomerase A1 (PDIA1/P4HB) is a molecular chaperone whose functions are essential for protein folding in the endoplasmic reticulum. Here we investigated the physiological requirement in vivo for PDIA1 in maintaining VLDL assembly and secretion. Methods: Pdia1/P4hb was conditionally deleted in adult mouse hepatocytes and the phenotypes characterized. Mechanistic analyses in primary hepatocytes determined how PDIA1 ablation alters MTTP synthesis and degradation as well as altering synthesis and secretion of Apolipoprotein B (APOB), along with complementary expression of intact PDIA1 vs a catalytically inactivated PDIA1 mutant. Results: Hepatocyte-specific deletion of Pdia1/P4hb inhibited hepatic MTTP expression and dramatically reduced VLDL production, leading to severe hepatic steatosis and hypolipidemia. Pdia1-deletion did not affect mRNA expression or protein stability of MTTP but rather prevented Mttp mRNA translation. We demonstrate an essential role for PDIA1 in MTTP synthesis and function and show that PDIA1 interacts with APOB in an MTTP-independent manner via its molecular chaperone function to support APOB folding and secretion. Conclusions: PDIA1 plays indispensable roles in APOB folding, MTTP synthesis and activity to support VLDL assembly. Thus, like APOB and MTTP, PDIA1 is an obligatory component of hepatic VLDL production.